MEMBANGUN KEMBALI KEPERCAYAAN PUBLIK TERHADAP KEPOLISIAN MELALUI PELAYANAN YANG RESPONSIF - Stevina Eka Sesaningrum; Hanny Purnamasari; Teza Yudha (LPPM Universitas Abdurrab, 2025)
The decline of public trust in the police institution has become a serious issue in the governance of democratic systems, particularly in urban areas such as Bekasi Regency. This study aims to understand how the community experiences, interprets, and responds to distrust toward the police, as well as its impact on legal participation and social relations. The author argues that distrust is not a form of resistance, but rather a reflective response to emotional experiences, unequal access to justice, and symbolic social legacies. This research fills a gap in academic literature, which has largely focused on quantitative performance evaluations of institutions, by employing a qualitative phenomenological approach within an interpretive paradigm to deeply explore citizens’ subjective experiences. The study was conducted in Bekasi Regency, involving five participants from diverse social backgrounds who were purposively selected. Data collection techniques included in-depth interviews, participatory observation, and contextual documentation. The findings reveal that distrust arises from convoluted bureaucratic procedures, inequality in legal treatment, as well as anxiety and insecurity within the legal process. Nevertheless, the community still holds hope for institutional change in the police through a more responsive, transparent, and humanistic service approach. These findings highlight the importance of public service reform based on social justice and participatory dialogue as strategies to sustainably rebuild public trust.